Agronomic Characteristics of Various Soybean Varieties (Glycine Max, Merril) Under Drought Stress Conditions - Yonny Koentjoro; Sukendah; F. Deru Dewanti (Nusantara Science and Technology Proceedings, 2023)
Drought conditions are a problem that is often found in soybean cultivation because in general soybeans are planted in the dry season where production is largely determined by the amount of water given. This study aims to evaluate the physiological and production characteristics of several soybean varieties under drought-stress conditions. 10 soybean varieties were tested at three levels of watering. This study was designed using a Completely Randomized Design with Factorial. The research was carried out in the experimental garden of the Faculty of Agriculture at Universitas Pembangunan Nasional Veteran Jawa Timur. The results showed that increasing the concentration of PEG given in the germination phase decreased germination, primary root length, and number of seminal roots. A significant interaction between varieties and water application occurs in the variable pod weight per plant. The genetic diversity of each variety tested showed differences in all of the observed variables. The decreasing availability of water affects all metabolism in plants, giving 50% of the normal requirement of water shows the lowest results in all observed variables. While giving 75% water is generally not significantly different from giving 100% water for normal needs